Molecular docking investigation of the amantadine binding to the enzymes upregulated or downregulated in Parkinson's disease - Mihaela Ileana Ionescu (International Association of Physical Chemists (IAPC), 2020)
Parkinson's disease (PD) is a progressive neurodegenerative disease. Levodopa in combination with amantadine has a demonstrated efficacy in motility impairment. An extensive investigation of some enzymes described to be upregulated or downregulated in PD was made - adenylate kinase (AK), adenine phosphoribosyltransferase (APRT), ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1), nucleoside-diphosphate kinase 3 (NDK3), purine nucleoside phosphorylase 1 (PNP1), and ecto-5'-nucleotidase (NT5E). Also, creatine kinase (CK) was included in the study because it is one of the main enzymes involved in the regulation of the nucleotide ratio in energy metabolism. To date, there is no proven link between amantadine treatment of PD and these enzymes. Because there are many AKs isoforms modified in PD, the AK was the first investigated. The molecular docking experiments allow the analysis of the selective binding of amantadine - unionized (with -NH2 group) and ionized form (with -NH3+ group) - to the AKs' isoforms implicated in PD. Using available X-ray 3D structures of human AKs in closed-conformation, it was demonstrated that there are notable differences between the interactions of the two forms of amantadine for the zebrafish AK1 (5XZ2), human AK2 (2C9Y), human AK5 (2BWJ), and AK from B.stearothermophilus. The cytosolic human AK1 and human AK2 mostly interact with ionized amantadine by AMP binding residues. The human AK5 interaction with ionized amantadine does not involve the residues from the catalytic site. Among other enzymes tested in the present study, APRT revealed the best results in respect of binding amantadine ionized form. The results offer a new perspective for further investigation of the connections between amantadine treatment of PD and some enzymes involved in purine metabolism.